2020
DOI: 10.33369/ijer.v2i1.10371
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Transformational Leadership, Interpersonal Communication, and Organizational Conflict on Organizational Effectiveness

Abstract: This study investigated whether the effect correlation exists between the Transformational Leadership, Interpersonal Communication, Organizational Conflict and Organizational Effectiveness in dayah in Aceh. Data were collected by questionnaires by 90 teachers in 3 pesantren, analysis using Path Analysis. The study found that the transformational leadership was most frequently employed, followed by the interpersonal communication, and then organizational conflict. The study found a positive effect transformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 6 publications
3
33
0
5
Order By: Relevance
“…Discussion 2: Hypothesis 2 Communication satisfaction was regressed on a simple linear regression with each of the three leadership predictors. Regarding the relationship between leadership styles and internet-based communication satisfaction, the study validates the research findings conducted by Terek et al (2015) and Mukhtar et al (2020), who proved a positive relationship between leadership and communication satisfaction. The current study showed that, when tested individually, the predictors of each of the leadership styles showed a positive and significant relationship with communication satisfaction in internet-based environments.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Discussion 2: Hypothesis 2 Communication satisfaction was regressed on a simple linear regression with each of the three leadership predictors. Regarding the relationship between leadership styles and internet-based communication satisfaction, the study validates the research findings conducted by Terek et al (2015) and Mukhtar et al (2020), who proved a positive relationship between leadership and communication satisfaction. The current study showed that, when tested individually, the predictors of each of the leadership styles showed a positive and significant relationship with communication satisfaction in internet-based environments.…”
Section: Discussionsupporting
confidence: 85%
“…By applying a path analysis, the researchers concluded a positive influence of transformational leadership, interpersonal communication, and organizational conflict towards organizational effectiveness. Regarding the relationship between communication and leadership variables, the study found a strong positive correlation between interpersonal communication and transformational leadership (Mukhtar et al, 2020).…”
Section: Literature Review and Hypothesesmentioning
confidence: 84%
“…With the existence of interpersonal communication carried out by the principal, it can have a good impact on the progress or quality of the school with a warning or giving advice from the principal, which can further improve teacher readiness in the teaching and learning process such as preparing materials or devices for teaching (Elfisa et al, 2020;Istiqomah et al, 2019;Marzuki & Tolla, 2019;Mukhtar et al, 2020;Murtiningsih et al, 2019;Wong & Daud, 2017). The importance of motivation in this work greatly determines how quickly organizational goals are achieved, both effectively and efficiently.…”
Section: Resultsmentioning
confidence: 99%
“…This behavior is formed by habituation, and changes in the knowledge system must precede habituation behavior. From several research results, Desfandi, (2017), Mukhtar et al, (2020) and Landriany, (2014) stated that the combination of effective leadership, high expectations (participation) of school members, and a stable system is a determining factor for program effectiveness.…”
Section: The Inhibiting Factors and Evaluation Of Adiwiyata Program Developmentmentioning
confidence: 99%